The Influence Of Persuasive Communication Competence And Librarian Performance On User Satisfaction At The Universitas Sumatera Utara Library - Ginting, Sinta Azhary; Dewi Kurniawati; Syafruddin Pohan (Social Science Studies, 2024)
Research Aims: This study aims to measure the influence of Persuasive Communication Competence on User Satisfaction at the Universitas Sumatera Utara Library, to measure the influence of Librarian Performance on User Satisfaction at the Universitas Sumatera Utara Library, Design/methodology/approach: This research employs a quantitative correlational method to understand the relationships between the variables. The Elaboration Likelihood Model (ELM) communication theory by Robert Cialdini is used in this study. The population for this study includes all individuals who have visited the Universitas Sumatera Utara Library. The sampling technique used is Accidental Sampling. The instrument used is a digital questionnaire distributed via Google Forms to 392 respondents. Research Findings: The results indicate that significant positive influence of both persuasive communication competence and librarian performance on user satisfaction at the Universitas Sumatera Utara Library. Persuasive communication and librarian performance can explain 58.4% of the influence on customer satisfaction, which according to the Guilford scale falls into the moderate/medium category and has a fairly high influence. The remaining 41.6% is influenced by other unmeasured variables such as physical facilities, collection availability, service systems, information technology, and human resources Theoretical Contribution/Originality: The results of this research can be used as a basis for further research on a larger scale or in a different context such as research in more general libraries. In addition, the researcher recommends that future researchers can carry out further research by conducting a more detailed investigation into the persuasive communication competencies of librarians and their role. Diverse approaches can provide a more comprehensive understanding of how librarians' persuasive communication competencies and performance influence library use.